Follow-up program in head and neck cancer. (May 2017) - De Felice, Francesca; de Vincentiis, Marco; Valentini, Valentino; Musio, Daniela; Mezi, Silvia; Lo Mele, Luigi; Terenzi, Valentina; D'Aguanno, Vittorio; Cassoni, Andrea; Di Brino, Martina; Tenore, Gianluca; Bulzonetti, Nadia; et al.
Highlights: Risk of local and distant recurrences is high in head and neck cancer (HNC). The role of adequate follow-up program in HNC is paramount. Worldwide several guidelines are available, but there is insufficient evidence to recommend one to others. We presented our reasonable follow-up scheme. This is the first reported follow-up program based on clinical and subclinical primary tumor evaluation. Abstract: Follow-up program in head and neck cancer (HNC) is an important issue in patients management. It represents the major dilemma in daily practice clinic. Many guidelines have been published in order to better define the best clinical protocol, but a consensus has not been attained yet. We constructed a follow-up program based on specific primary subsite, to standardize patients surveillance after treatment of HNC.